Relativas cortadoras: mover e cortar? Ou cortar antes de mover? - Espírito Santo, Ana (Revista da Associação Portuguesa de Linguística, 2020)
With this article, we aim at providing an answer to two main theoretical questions: what is the syntactic derivation of European Portuguese P-chopping relative clauses? And what is the nature of the phonetically and semantically null element that integrates them? We also attempt to identify constants that allow us to predict other lexical contexts for the occurrence of P-chopping relative clauses other than the ones already described in the literature. We support our conclusions with the data collected in an acceptability judgment task that included 76 native speakers. Our proposal is a derivation for P-chopping relative clauses similar to the existing one for direct object relative clauses, assuming that the null element that integrates them has the properties of a variable.